(untitled) - Williams, John Hoyt (New York, 1988)
The Union Pacific and Central Pacific Railroads were officially joined on May 10, 1869 at Promontory Point, Utah, with the driving of a golden spike. This historic ceremony marked the completion of the first transcontinental railroad. Spanning the Sierras and the “Great American Desert,” the tracks connected San Francisco to Council Bluffs, Iowa. A Great and Shining Road is the exciting story of a mammoth feat that called forth entrepreneurial daring, financial wizardry, technological innovation, political courage and chicanery, and the heroism of thousands of laborers.
Keywords: Pacific railroads,Railroads; History,History; West ( U.S.)